Process Development Process Problem Based Learning for Writing Students' Explanatory Texts in Class XI SMK PAB 03 Medan - Dinny Andriani Purba; Syahnan Daulay; Marice Marice (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2020)
This study aims to describe the process of developing problem-based learning models (Problem Based Learning) to write explanatory texts of students in class XI SMK PAB 03 Medan. This research was conducted at SMK PAB 3 Medan located on Jl. Mosque No. 1, Medan Estate, Medan, Medan Baru District The research will be conducted in July 2019 to October 2019. The population of this research is all students of class XI SMK PAB 3 Medan in 2019/2020 academic year. The process of developing problem-based learning models on explanatory text writing material in class XI students of SMK PAB 03 Medan is in general aspects of the assessment given by reviewers, the product design of problem-based learning model development is very good (SB) with an average overall score of 89.5% with very good assessment criteria.